A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil - Pereira, Thiago N.a.; Lucinda, Paulo H.f. (Zootaxa, 2007)
A new characid species, Jupiaba elassonaktis, is described from the rio Tocantins drainage. The new species is distinguished from its congeners by the following combination of characters: medial cusps of premaxillary teeth much larger than remaining cusps, dentary teeth decreasing abruptly in size from the fifth tooth backwards, first dorsaland anal-fin rays not prolonged by an elongate filament, presence of a vertically elongate humeral spot, 33–39 scales on lateral line, 5–7 scales series above lateral line, 9–11 pectoral-fin rays, and a incomplete series of median predorsal scales.